Synthesis and Charcterization of Coupled ZnO/SnO2 Photocatalysts and Their Activity towards Degradation of Cibacron Red Dye. Issue 1 (2nd January 2018) - Verma, Naveen; Yadav, Suprabha; Marí, Bernabe; Mittal, Anuj; Jindal, Jitender
ABSTRACT: A series of coupled ZnO-SnO2 photocatalyst was successfully synthesized in the Zn:Sn molar ratio of 20:1, 10:1, 5:1 and 2:1 via co-precipitation method followed by calcination at different temperatures. The synthesized materials were characterized by X-ray diffraction, diffuse reflectance spectra, scanning electron microscope and transmission electron microscope. Photocatalytic activitiy of synthesized materials was applied for the degradation of cibacron red dye in aqueous solution under UV-A light irradiation. Experimental results revealed that the coupled ZnO-SnO2 photocatalyst with Zn:Sn molar ratio 10:1, calcined at 600oC for 1 h was the most efficient photocatalyst among synthesized samples for the degradation of cibacron red. Superoxide anion radical ( O2 – ) was found to be the prominent active species responsible for degradation comparative to hole (h + ), hydroxyl radical ( OH). GRAPHICAL ABSTRACT: